2015
DOI: 10.1021/acscatal.5b01779
|View full text |Cite
|
Sign up to set email alerts
|

Water as a Promoter and Catalyst for Dioxygen Electrochemistry in Aqueous and Organic Media

Abstract: Water and oxygen electrochemistry lies at the heart of interfacial processes controlling energy transformations in fuel cells, electrolyzers, and batteries. Here, by comparing results for the ORR obtained in alkaline aqueous media to those obtained in ultra-dry organic electrolytes with known amounts of H 2 O added intentionally, we propose a new rationale in which water itself plays an important role in determining the reaction kinetics. This effect derives from the formation of HO ad ···H 2 O (aqueous soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
115
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 44 publications
9
115
1
Order By: Relevance
“…This would be in agreement with the proposals for the ORR on Au(100) in alkaline electrolyte in a recent theoretical study . Alternatively, the OH ad could be directly involved in the reaction, for instance, by interaction of the OH ad moiety with the activated water molecule, enabling a proton transfer to an adsorbed superoxide, as proposed recently . In another study, the authors proposed that double‐bridge sites as present on Au(100) promote the dissociation of adsorbed OOH in the 4‐electron ORR in alkaline electrolyte .…”
Section: Resultssupporting
confidence: 88%
“…This would be in agreement with the proposals for the ORR on Au(100) in alkaline electrolyte in a recent theoretical study . Alternatively, the OH ad could be directly involved in the reaction, for instance, by interaction of the OH ad moiety with the activated water molecule, enabling a proton transfer to an adsorbed superoxide, as proposed recently . In another study, the authors proposed that double‐bridge sites as present on Au(100) promote the dissociation of adsorbed OOH in the 4‐electron ORR in alkaline electrolyte .…”
Section: Resultssupporting
confidence: 88%
“…Considering that the potential scan in the present study extends by about 0.9 V after the initial onset of the ORR one would expect to see this feature again, but it was neither observed in stagnant electrolyte nor for any of the rotation rates applied. We tentatively explain this difference by a lower water content in the present study under controlled glovebox atmosphere, as water is known to have a promoting effect on the ORR in aprotic electrolytes . Between approx.…”
Section: Resultsmentioning
confidence: 99%
“…This was similar to the potential at which Sawyer et al 39 reported oxidation peaks in the presence of protons (from added HClO 4 ) and also close to the potential at which oxidation peaks were observed with the addition of water. 44 The voltage range from 1.85 V to 4.35 V covered the operating range of Li-air cells wherein the discharge and charge plateaus were found to occur at ∼2.5 V and ∼4 V respectively. Upon saturation with oxygen, the voltammograms showed a reduction peak below 2.45 V and oxidation peak above 2.65 V during the cathodic and anodic scans respectively on GC, Pt and Au, with a voltage separation whose magnitude suggested a degree of irreversibility.…”
Section: Resultsmentioning
confidence: 96%